2015
DOI: 10.5152/tpa.2015.2167
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of selective head cooling therapy and whole body cooling therapy in newborns with hypoxic ischemic encephalopathy: Short term results

Abstract: Aim: In this study, it was aimed to investigate which method was superior by applying selective head cooling or whole body cooling therapy in newborns diagnosed with moderate or severe hypoxic ischemic encephalopathy. Material and Methods: Newborns above the 35th gestational age diagnosed with moderate or severe hypoxic ischemic encephalopathy were included in the study and selective head cooling or whole body cooling therapy was performed randomly. The newborns who were treated by both methods were compared i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…These two neuroprotections are similar, and whole-body cooling had a greater effect on the suppression of radical production than head cooling (Ikeda et al, 2012). A research study comparing selective head cooling therapy with whole body cooling therapy in newborns with hypoxic ischemic encephalopathy uncovered no difference between the two methods in terms of adverse effects and short-term results (Atici et al, 2015). Other research studies have also reached similar conclusion about hypoxic ischemic encephalopathy (Sarkar et al, 2009a,b; Celik et al, 2016).…”
Section: Hypothermia Induction Methodsmentioning
confidence: 99%
“…These two neuroprotections are similar, and whole-body cooling had a greater effect on the suppression of radical production than head cooling (Ikeda et al, 2012). A research study comparing selective head cooling therapy with whole body cooling therapy in newborns with hypoxic ischemic encephalopathy uncovered no difference between the two methods in terms of adverse effects and short-term results (Atici et al, 2015). Other research studies have also reached similar conclusion about hypoxic ischemic encephalopathy (Sarkar et al, 2009a,b; Celik et al, 2016).…”
Section: Hypothermia Induction Methodsmentioning
confidence: 99%
“…In the present study, there were significant correlations between the severity of HIE in neonates and the need for mechanical ventilation and 55% of newborns who underwent mechanical ventilation died. Atıcı et al [ 39 ] demonstrated 94% of HIE infants during the cooling process require mechanical ventilation and no differences were found between the 2 cooling methods. The involvement of other organs, including the lung, worsens the prognosis of neonatal HIE.…”
Section: Discussionmentioning
confidence: 99%
“…The requirement for invasive mechanical ventilation, ability to perform extubation during the period of cooling and risk of PPHN were analyzed in two studies [25,27]. No differences were found between groups in regard to the need of mechanical ventilation during the cooling or ability to be extubated during the cooling.…”
Section: Discussionmentioning
confidence: 99%